Safe trip: Factors contributing to slip, trip and fall risk at train stations. (April 2021) - Larue, Grégoire S.; Popovic, Vesna; Legge, Matthew; Brophy, Claire; Blackman, Ross
Abstract: Public transport systems are vital services in urban environments. The design of these complex socio-technical systems is continuously evolving to accommodate larger populations, and their adaptation is essential in supporting the successful and sustainable development of cities and regions. An essential part of this adaptation includes working to increase passenger safety and to minimise their risk of injury. With this focus, key objectives of the current study were to identify the causes of slip, trip and fall (STF) incidents attributable to the rail user and to train and station characteristics. An investigation of historical STF records of 1247 train and station incidents in two Australian jurisdictions was conducted. Various contributing factors to STF events were identified, including locations such as stairs, ramps, escalators, the train's entry and exit step, doorway areas, and passenger running or rushing. A mixed-method field study was then conducted at three train stations and on trains. To further investigate the contributing factors, participants (N = 40) wore an eye tracker as they navigated the stations and trains. The research illustrates that their continuous search for information, and a disconnect between the information needed and the information provided, might be a cause of passenger distraction and an increase in their risky behaviour. Therefore, we suggest that improvements in information design to reduce the high visual workload for passengers might also reduce the incidence of STFs. Highlights: Slips, Trips and Fall (STF) events is a high safety priority for rail operators. A list of behaviours leading to STFs based on the literature and historical data was identified. Field observations with eye-tracker and retrospective interviews provided new insights. Passengers were searching continuously for information that was incomplete. High cognitive and information processing workload might cause STFs.